Destruction of the overworld : an unofficial Minecrafter's adventure - Cheverton, Mark (Herobrine reborn ;, 2015)
After Gameknight999 and his father banish the evil virus Herobrine to the Void, the Ender Dragon escapes and they must find a way to defeat the dragon without releasing Herobrine.